Comparison Of Naso Faring And Oro Pharynx Swab Samples On Positivity Rate For Covid – 19 With The Reverse Transcription Method Pcr (Rt–Pcr) In The Lab. Rsud Pcr. City Padang Sidempuan - Sihombing, Yanna Rotua; Romauli Anna Teresia Marbun; Lenni Rismayanti; Ratih Anggraeni; Octavian Ashido Nababan; Kristian Cahayani Zebua (Jurnal FARMASIMED (JFM), 2024)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) could be a coronavirus that causes COVID-19 infection. SARS-CoV-2 is classified as an RNA infection that can cause gentle to severe respiratory diseases. Viral contaminations proceed to extend quickly, so it is critical to prevent the spread of the infection through nasopharyngeal and/or oropharyngeal swabs within the community. The point of this consider was to decide the exactness of nasopharyngeal or pharyngeal spread testing and the inspiration rate in RSUD patients. Padang Sidempuan City This think about was performed by collecting 20 nasopharyngeal swabs and 20 pharyngeal swabs from RSUD patients. City of Padang Sidempuan Infection testing was performed within the research facility by turn around transcriptase polymerase chain response (RT-PCR). Information were analyzed employing a chi-square test with p < 0.05. Judging from the nasopharynx and oropharynx positive rate comes about, the nasopharynx positive rate esteem is higher than the nasopharynx positive rate esteem, indeed in case it is the same persistent. The conclusion of this ponder is that the discovery of SARS-CoV-2 by nasopharyngeal swab will be more precise.